Valorisation of goldenberry calyx: ultrasound-assisted extraction of phenolic compounds - TOBAR-DELGADO, Elizabeth; TORRES-CASTAÑEDA, Harlen; SERNA-COCK, Liliana; OSORIO-MORA, Oswaldo; TIRADO, Diego F. (Food Science and Technology, 2023)
The extraction of value-added compounds from agro-industrial wastes is important to reduce their environmental impact. In this research, the time for ultrasound-assisted extraction of phenolic compounds obtained from goldenberry (Physalis peruviana L.) calyx was first chosen. Subsequently, response surface methodology was used to optimise the effect of wave amplitude, liquid:solid ratio, and particle size on total phenol content and in vitro antioxidant capacity. Then, antioxidant capacity (DPPH, 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), and ferric reducing antioxidant power) was measured in the extract obtained under optimal conditions, and rutin flavanol was identified and quantified by HPLC-DAD. Analysis of polynomial models indicated adequate fit (p≤0.05) for phenolic content (R2=0.98) and antioxidant capacity (R2=0.91). Optimal amplitude (54%), liquid:solid ratio (33 mL/g), and particle size (213 µm) maximised the response of phenolic content (53 mg GAE/g) and antioxidant capacity (167 μmol TE/g). The in vitro antioxidant capacity of the extract was demonstrated, and a high rutin concentration (19 mg/g) was found in the extract obtained under optimum conditions. High extraction yields of phenolic compounds were found using the shortest time (i.e., 10 min), intermediate particle diameters, a low amount of solvent, and low energy consumption.